Comparative evaluation of intraocular pressure with an air-puff tonometer versus a Goldmann applanation tonometer - Farhood QK (Dove Medical Press, 2012)
Qasim K FarhoodDepartment of Ophthalmology, College of Medicine, University of Babylon, Babylon, IraqPurpose: Tonometry, or measurement of intraocular pressure (IOP), is one of the most important examination procedures in ophthalmic clinics, and IOP is an important parameter in the diagnosis of glaucoma. Because there are numerous types of tonometer available, it is important to evaluate the differences in readings between different tonometers. Goldmann applanation tonometers (GATs) and noncontact air-puff tonometers (APTs) are largely available in ophthalmic clinics. The purpose of this study was to evaluate the role of AP tonometer by comparing the measurements of IOP made using this device with those made using a GAT.Patients and methods: This study involved 196 eyes from 98 study participants, all of whom were patients attending an ophthalmic outpatient clinic. Each patient's IOP was measured using both Goldmann applanation tonometry and AP tonometry, and the difference in readings between the two methods was calculated.Results: The mean IOP as measured by GAT was 13.06 ± 4.774 mmHg, while that as measured by AP tonometer was 15.91 ± 6.955 mmHg. The mean difference between the two methods of measurement was 2.72 ± 2.34 mmHg. The readings obtained by AP tonometer were higher than those obtained by GAT in 74% of patients, and this difference was most obvious when the GAT measurement of IOP exceeded 24 mmHg. No statistically significant variation in IOP was noted between the devices when the patients' age, sex, and laterality (right and left eyes) were considered.Conclusion: There is a significant difference in the measurement of IOP between GATs and AP tonometers. Goldmann applanation tonometry remains the most suitable and reliable method for measuring IOP. Because measurements of IOP by AP tonometer are usually higher than those obtained by GAT regardless of the patient's age, sex, or laterality of eyes, AP tonometry is a suitable method for community or mass screenings of IOP.Keywords: tonometry, comparison, glaucoma, noncontact tonometry, goldmann applanation tonometer